Correlation of glutamine and serial absolute neutrophil count as a parameter of infection in major burn trauma patients at Sanglah General Hospital, Bali, Indonesia - Shita Diwyani Sudarsa; Agus Roy Rusly Hariantana Hamid; Agustinus I Wayan Harimawan; Ni Nyoman Sri Budayanti (Intisari Sains Medis, 2021)
Background: Burns are thermal trauma that often results in high morbidity. In major burns, gastrointestinal dysfunction plays a vital role in the progression of infection to organ failure. Glutamine is a pharmaconutrient that has important implications for burn patients, including in the prevention of infection. This study evaluates the relationship between glutamine administration and the serial absolute neutrophil count as a parameter for infection incidence in patients with major burns.Methods: This study was an analytical study with a cross-sectional design to see the relationship between glutamine administration and the serial absolute neutrophil count levels of major burn patients at Sanglah General Hospital. The sample consisted of 56 patients from the medical records of burn patients. The data were extracted from the medical records and then inserted into the data collection sheet. Then performed data analysis using SPSS version 21 for Windows.Results: Bivariate analysis showed that there was a significant difference between glutamine administration and the absolute neutrophil count levels on days 3, 5, and 14 (p = 0.004, 95% CI: 1.70-8.46), (p = 0.000, 95% CI: 2.71-7.83), and (p = 0.035, 95% CI: 0.61-7.27), respectively. This showed that patients given glutamine had lower neutrophil levels on days 3, 5, and 14 than patients who were not given glutamine. Multivariate analysis confirmed that glutamine administration did independently affect and decrease the absolute neutrophil count levels on days 3, 5, 14, and the mean without being influenced by other variables with p value = 0.004 (95% CI: [-8.445] - [-1,732]), p = 0.000 (95% CI: [-7,808]-[-2,743]), p = 0.020 (95% CI: [-7.251]-[-0.639]), and p = 0.017 (95% CI: [-5,815]-[-0.588]), respectively.Conclusion: This study has shown that glutamine administration was significantly associated with and decreased the serial absolute neutrophil count in major burn patients.